Acrylic fusion : experimenting with alternative methods for painting, collage, and mixed media - Tranberg, Dan (Quarry Books, 2012)
"Acrylic Fusion is a unique reference book, designed to excite and motivate artists to push beyond traditional techniques and to explore new approaches to painting. Acrylic Fusion is predicated on the idea that many working artists, whether they went to art school or not, tend to think of painting technique in terms of what is correct or permissible. This mindset stifles creativity and prevents discovery. By contrast, Acrylic Fusion sets artists free by exposing them to a diverse range of alternative techniques, unconventional processes, and integration of unique materials that stimulate creativity and encourage experimentation. Acrylic Fusion is a must-have resource aimed at artists who make paintings, but is also a great reference for any crafters, makers and DIYers who use paint in their work, whether they make art journals, design greeting cards, or refinish furniture since the techniques can easily be adapted for many different kinds of projects and applications"--Provided by publisher.